DOI: 10.33915/etd.1080
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of glass fiber-reinforced composite/wood railroad crossties

Abstract: DEVELOPMENT AND EVALUATION OF GLASS FIBER REINFORCED COMPOSITE/WOOD RAILROAD CROSSTIES Krit Laosiriphong Railroad crossties are strengthened by wrapping glass fiber reinforced composites (GFRC). In addition, durability of crossties has been found to have enhanced by reinforcing them with GFRC wraps. In order to reduce the cost, GFRC wraps are not used to wrap the entire length of a crosstie, but only in the region that holds steel plates. The objective of this research is to select compatible adhesive between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…He developed more accurate environmental reduction factors than those given by the design codes. Laosiriphong (2000) found that the use of GFRP wraps increased the durability of railroad crossties and enhanced the flexural rigidity by 44% and the shear modulus by 18%. Memon and Sheikh (2005) investigated the use of GFRP sheets to repair square columns under simulated earthquake loads.…”
Section: Fig 4 Schematic Of Damaged Sectionmentioning
confidence: 99%
“…He developed more accurate environmental reduction factors than those given by the design codes. Laosiriphong (2000) found that the use of GFRP wraps increased the durability of railroad crossties and enhanced the flexural rigidity by 44% and the shear modulus by 18%. Memon and Sheikh (2005) investigated the use of GFRP sheets to repair square columns under simulated earthquake loads.…”
Section: Fig 4 Schematic Of Damaged Sectionmentioning
confidence: 99%
“…Yan [31] investigated the durability of GFRP as bridge deck reinforcement subject to weathering conditions. Laosiriphong [18] found that the use of GFRP wraps increased the durability of railroad crossties and enhanced the flexural rigidity by 44 % and the shear modulus by 18 %. Memon and Sheikh [20] investigated the use of GFRP sheets to repair square columns under simulated earthquake loads.…”
Section: Introductionmentioning
confidence: 99%
“…However, Talakanti [22] showed that under a maximum applied strain of 4500 microstrains, after 2 million fatigue cycles, a GFRP wrapped wood specimen retains about 60% stiffness while an unwrapped wood specimen fails at 0.5 million cycles. Work currently in progress, being done by researchers at the Constructed Facilities Center (Chamarthy [23] and Laosiriphong [24]) also showed that the GFRP wrapping increases the properties of wood upto 100%. We speculate that The following observations were made from Figure 6.6:…”
Section: Sample Conditioningmentioning
confidence: 99%